2019
DOI: 10.3171/2019.8.focus19621
|View full text |Cite
|
Sign up to set email alerts
|

Reliable navigation registration in cranial and spine surgery based on intraoperative computed tomography

Abstract: OBJECTIVELow registration errors are an important prerequisite for reliable navigation, independent of its use in cranial or spinal surgery. Regardless of whether navigation is used for trajectory alignment in biopsy or implant procedures, or for sophisticated augmented reality applications, all depend on a correct registration of patient space and image space. In contrast to fiducial, landmark, or surface matching–based registration, the application of intraoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 33 publications
0
50
0
Order By: Relevance
“…ED for the control scan was 4.51 ± 2.48 mSv. Segmentation of the implant and its visualization with updated AR allowed the checking of patient accuracy and patient registration, image registration, and AR calibration [ 20 ]. In this series, no revision surgeries were needed following control iCT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ED for the control scan was 4.51 ± 2.48 mSv. Segmentation of the implant and its visualization with updated AR allowed the checking of patient accuracy and patient registration, image registration, and AR calibration [ 20 ]. In this series, no revision surgeries were needed following control iCT.…”
Section: Resultsmentioning
confidence: 99%
“…However, this strategy is not applicable to the lateral approach to the spine because it can be implemented only in posterior open surgery. In spine procedures, fiducial-based registration is an option only when intraoperative imaging is available, because flexibility of the spine precludes the vertebra alignment during the preoperative scan being identical to the intraoperative alignment [ 20 , 22 ]. User-independent registration can be achieved by intraoperative imaging, which, regarding spinal surgery, has the additional advantage that the positioning of the patient and vertebral alignment during imaging correspond to the real intraoperative situation.…”
Section: Discussionmentioning
confidence: 99%
“…In this workflow, the Dynamic Reference Frame is fixated intra-operatively, and during acquisition of a Cone-Beam CT (CBCT) the DRF is tracked with the optical camera 7,10,12,30 . This method yields an accurate registration, even if low-dose scan protocols are used, but may lead to an increase in operation time and pose logistical challenges intra-operatively 10,12 . A compatible intra-operative scanner is required, and currently, this method is only available for optical tracking.…”
Section: Discussionmentioning
confidence: 99%
“…The same authors showed that the techniques currently employed in cranial surgery for HUD can be applied to spine tumor surgery (35). In a separate publication, they demonstrated that intraoperative CT can be used with a low-dose protocol for AR registration in spine cases with registration errors of less than 1 cm and 70% decrease in overall radiation exposure, which can further facilitate AR usage in spine surgery (36). Müller et al explored the use of 3D intraoperative fluoroscopy for AR registration (37).…”
Section: Workflows For Registrationmentioning
confidence: 99%